2016
DOI: 10.1002/ajpa.23002
|View full text |Cite
|
Sign up to set email alerts
|

Canine and incisor microwear in pitheciids and Ateles reflects documented patterns of tooth use

Abstract: These findings align with expectations from reported field observations of tooth use and illustrate the potential for using microwear texture analysis to infer patterns of anterior tooth use in extinct primates. Am J Phys Anthropol 161:6-25, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 120 publications
(347 reference statements)
3
13
0
Order By: Relevance
“…The pitheciids in this study represent differing levels of hard/tough seed reliance within their diets. As expected, given observations that the anterior teeth are responsible for initial seed processing in these taxa, the incisor and canine microwear reveal differences in feature depth and complexity between pitheciines and Callicebus (Delezene et al, ). Other seed‐eating genera, like mangabeys, process food with their molars, and display molar microwear differences in heterogeneity and anisotropy from leaf eaters.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The pitheciids in this study represent differing levels of hard/tough seed reliance within their diets. As expected, given observations that the anterior teeth are responsible for initial seed processing in these taxa, the incisor and canine microwear reveal differences in feature depth and complexity between pitheciines and Callicebus (Delezene et al, ). Other seed‐eating genera, like mangabeys, process food with their molars, and display molar microwear differences in heterogeneity and anisotropy from leaf eaters.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to these six SSFA measures, eight International Organization for Standardization (ISO 25178–2) measures were used to evaluate the microwear scans (following Calandra, Schulz, Pinnow, Krohn, & Kaiser, ; Delezene et al, ; Purnell, Seehausen, & Galis, ; Schulz et al, ) (Table ). It has been suggested that SSFA measures correlate with food type intake, while ISO measures better reflect the functional interaction between food and teeth (Calandra et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of only three other studies of microwear texture and diet on non-occlusal tooth surfaces, but none were based on ISO parameters, so direct comparison of texture attributes with our study is not possible. Nonetheless, these studies found significant relationships between diet/feeding and microwear textures on the labial surfaces of shrew incisors 53 , the labial surfaces of incisors in platyrrhine primates (New World primates) 54 and the buccal surfaces of molars in catarrhine primates (Old World primates) 55 .…”
Section: Discussionmentioning
confidence: 94%
“…Dental microwear texture analysis (DMTA) is a method of dietary reconstruction based on interpreting micro‐features as they appear on dental enamel. Since 2005, researchers have demonstrated its efficacy via comparative and experimental studies using extinct and extant organisms (e.g., Calandra, Schulz, Pinnow, Krohn, & Kaiser, ; Delezene, Teaford, & Ungar, ; DeSantis, Schubert, Scott, & Ungar, ; Estalrrich & Rosas, ; Purnell & Darras, ; Ragni, Teaford, & Ungar, ; Schulz, Calandra, & Kaiser, ; Scott et al, ; Scott et al, ; Scott, Teaford, & Ungar, ; Shearer et al, ; Teaford & Ungar, ; Teaford, Ungar, Taylor, Ross, & Vinyard, ; Ungar, Grine, & Teaford, ). Specifically, the DMTA derived from living primates has been especially integral in the contextualization of fossil primate and hominin diets (e.g., Delezene, Zolnierz, Teaford, Grine, & Ungar, ; El Zaatari, Grine, Ungar, & Hublin, ; Grine, Ungar, Teaford, & El Zaatari, ; Karriger, Schmidt, & Smith, ; Scott et al, ; Ungar, ; Ungar et al, ; Ungar, Krueger, Blumenschine, Njao, & Scott, ; Ungar & Scott, ; Ungar, Scott, & Steininger, ; Ungar & Sponheimer, ) and recent experimental work has allowed us to better understand the mechanics of microwear formation (e.g., Daegling, Hua, & Ungar, ; Hua, Brandt, Meullenet, Zhou, & Ungar, ; Xia et al, , ).…”
mentioning
confidence: 99%